From Policy to Practice: Exploring Inclusive School Culture in Vocational Education through the Index for Inclusion - Hidayat, Nur; Miftahul Alam Al Waro’; Rifqi Minchatul ‘Ulya (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to explore inclusive school culture through a vocationally adapted Index for Inclusion framework, focusing on multistakeholder perspectives and the factors shaping inclusive practices in vocational school settings. Employing a qualitative case study design at a vocational high school (SMK) in Surabaya, Indonesia, the study applies an Index for Inclusion framework extended with a fourth dimension, Vocational Accessibility & Transition Readiness (VATR), which integrates vocational pedagogy, Universal Design for Learning, and a school-to-work transition framework. Ten stakeholders were purposively selected using a maximum variation sampling strategy. Data were collected through triangulation of semi-structured interviews, participant observation, and document analysis, using an instrument developed from the operationalization of 24 Index for Inclusion sub-indicators. Data were analyzed using Braun and Clarke’s six-phase thematic analysis with a deductive–inductive approach. Based on scores across 12 core Index for Inclusion indicators, the findings showed an overall inclusion attainment of only 41.67%, characterized by covert selectivity, a 1:12 special education teacher (GPK)-to-student ratio, inaccessible infrastructure, and declining academic expectations. Notably, a gap emerged between teachers’ strength-based perceptions of students with disabilities and the exclusionary experiences reported by the students themselves, indicating that students’ vocational potential is evident but remains systemically unsupported. This study proposes a Vocational Universal Design for Learning (V-UDL) framework to reconcile industry standardization with inclusive differentiation, while strengthening the VATR dimension as a policy foundation for strength-based major placement, improved special education teacher ratios, and the development of inclusive vocational learning modules at the SMK level.